PENGARUH MANAJEMEN RISIKO TERHADAP KINERJA KEUANGAN (STUDY PADA PERBANKAN SYARIAH YANG TERDAFTAR DI BEI) - Mardiana, Mardiana (IQTISHODUNA, 2018)
Abstract: The objectives of this research to analize the influence risk management is as proxy of Capital Adequacy Ratio (CAR), Operation Efficiency (BOPO), Non Performing Loan (NPL), to Financial Performance is as proxy of Return on Asset (ROA) Banking Firms wich listed on BEI in 2011 until 2016 periods. This research using time series data from Bank Indonesia’s published financial reports Banking Firms wich listed on BEI in 2002 until 2007 periods. After passed the purposive sampling phase, the number of valid sample is 5 Banking Firms wich listed on BEJ. The result of this research shows that CAR and NPL variables has a negative and unsignificant influence to ROA. BOPO variable also has a significant influence to ROA, the distinction between BOPO than another variables is the sign of variable coefficient, it has negative coefficient. It’s mean that the bank managements should be concern on the BOPO variable to improve profitability on their Financial Performance. Disintermediary functions of bank that occurs in the research periods is the reason for unsignificant CAR and NPL variable to ROA variable wich is as a proxy of Financial Performance Banking Firms.